Impact of Total Quality Management on Customer Satisfaction for Malaysia’s Telecommunication Sector in Selangor - Mohamad, Arifha; MOHAMED SABRI, INTAN NURJANNAH (Research in Management of Technology and Business, 2022)
Customer satisfaction is one of the major concern today. Every feature and aspect of the service industry should be investigated with the aim of advancing and developing service quality and resolving problems that occur to the customer, creating customer values, achieving customer satisfaction and establishing sustainability for business. As a result, every company or organisation invested more in quality improvements. These efforts resulted in a new quality management method known as total quality management (TQM). TQM assist telecommunication industry in retaining and acquiring satisfaction of the customer. Therefore, the intention of the study is to identify the relationship between customer satisfaction and TQM in Malaysia’s telecommunication sector.